Pengaruh pemberian ekstrak daun manisrejo terhadap perubahan kadar SGOT dan SGPT kelinci pedaging - Nur Rahman; Gebby Putri Nurhaida; Dwipajati Dwipajati (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Manisrejo leaves (Vaccinium Varingifolium) contain flavonoids, steroids, tannins and triterpenoids. flavonoid are antioxidant compounds which are believed to have the ability to bind active oxygen radicals, superoxide and hydroxyl radicals through a single electron transfer. The properties of flavonoids besides protecting the effects of ROS on cells can also inhibit the formation of ROS and can reduce levels SGOT and SGPT. In conditions of liver disorders there is an increase in liver enzymes that cause changes in SGOT and SGPT levels. Antioxidant compounds can overcome liver damage caused by free radicals.Objectives: Analyzed the effect of giving Manisrejo leaf extract to changes in body weight and SGOT SGPT levels in broiler rabbits.Method: This research is a type of laboratoryan experimental research conductedstudy on meat rabbits by giving Manisrejo leaf extract to analyze changes in body weight and SGOT SGPT levels of meat rabbits. The research was carried out in May – June 2023 at the Chemistry Laboratory of the Health Polytechnic, Malang Ministry of Health, Malang in May-June 2023 Health Polytechnic. The samples used in the research were 30 meat rabbits. Research data includes the rabbit's body weight taken throughby weighing and SGOT SGPT data obtained through laboratory testing using kinetic methods before and after the intervention. Analysis of research data to test the normality of the data uses the Shapiro Wilk test, then if the data is normal, use the One Way ANOVA statistical test, if the distribution is not normal, use the Kruskal Wallis Test at a confidence level of 95%.Results: There is an increase in rabbit body weight before and after intervention with a p value of 0,001 which indicates that there is a significant difference between rabbit body weight before and after intervention. Statistical test results p value 0,198 which indicates there is no significant difference between the administration of manisrejo leaf extract at the SGOT level and p value 0,180 which indicates there is no significant difference between the administration of manisrejo leaf extract at the SGPT level.Conclusion: There is no effect of giving Manisrejo leaf extract on changes in SGOT and SGPT levels in broiler rabbits.KeywordsBroiler Rabbit, Manisrejo Leaf Extract, SGOT, SGPT